Fiscal and monetary policies in the BRICS: a panel VAR approach - Jawadi, Fredj (2016)
Using a Panel Vector Auto-Regressive (PVAR) model, we assess the macroeconomic impact of fiscal policy and monetary policy shocks for five key emerging market economies—Brazil, Russia, India, China and South Africa (BRICS). We show that monetary contractions lead to a fall in real economic activity and tighten liquidity market conditions, while government spending shocks have strong Keynesian effects. We also find evidence supporting the existence of accommodative stance between fiscal policy and monetary policy, which is crucial for economic and political decision-making. Our results are robust even after controlling for periods of extreme instability, such as economic and financial crises.